KEPASTIAN HUKUM COVERNOTE NOTARIS TERHADAP PEMBERIAN FASILITAS KREDIT DARI BANK YANG BERUJUNG PADA TINDAK PIDANA KHUSUS - Brigita febiastari. A; Dhody AR Widjajaatmadja; Wayan Karya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
In the process of granting credit facilities by the bank, the Notary as a bank partner has the role to publish a covernote regarding legal acts that have been committed before the Notary as well as those that are still in process of settlement by the Notary so that the bank has a underlying to disburse the credit. Recent phenomena indicate that Notaries do not properly fulfill their duties and responsibilities appropriately in connection with the covernote they have made, causing losses to the bank and leading to Notaries allegedly being involved in fraud that ends in corruption criminal acts. The Notary rule out what was supposed to be done in the issue of the covernote so there was no guarantee of legal certainty for the covernote made by the Notary. The problems in this research are how the Notary's responsibility in connection with the covernote that they made to the issue of the provision of credit facilities from the bank that ended in a special criminal acts? And how is the legal certainty of a Notary's covernote against the provision of credit facilities from the bank that ended in a special criminal acts? The theory used in this research are the theory of legal certainty according to Jan Michiel Otto and the theory of responsibility according to Hans Kelsen. The method used in this research is normative juridical research, specifically a library law research or secondary data with primary, secondary, and tertiary legal sources. As for the research approach used are statute approach, case approach, conceptual approach, and analytical approach and the method of collecting the legal materials are carried out by identifying and taking an inventory of positive law, journals, and other legalsources. The method used in analyzing the legal materials are law grammatical interpretation and systematic interpretation, and the method used of legal construction are Analogi and Argumentum A Contrario.